Exacerbated lung inflammation in offspring with high maternal antibody levels following secondary RSV exposure - Ma, Jinhua; Gong, Ting; Luo, Tingting; Li, Shuanglian; Zhong, Li; Zhao, Xin; Mei, Chenghao; Bu, Huaqin; Jia, Zhenxing; Kuang, Xiaohu; Wang, Xiaoli; Fu, Zhou; et al. (Frontiers in Immunology, 2024)
Respiratory syncytial virus (RSV) is the primary cause of bronchiolitis-related hospitalizations among children under 5 years of age, with reinfection being common throughout life. Maternal vaccination has emerged as a promising strategy, delivering elevated antibody levels to newborns for immediate protection. However, limited research has explored the protective efficacy of maternal antibodies (matAbs) against secondary RSV infections in offspring. To address this gap, we employed a mouse model of maternal RSV vaccination and secondary infection of offspring to evaluate lung pathology following RSV reinfection in mice with varying levels of maternal antibody (matAb). Additionally, we aimed to investigate the potential causes of exacerbated lung inflammation in offspring with high matAb levels following secondary RSV exposure. Our findings revealed that offspring with elevated levels of maternal pre-F antibody demonstrated effective protection against lung pathology following the initial RSV infection. However, this protection was compromised upon reinfection, manifesting as heightened weight loss, exacerbated lung pathology, increased expression of RSV-A N genes, eosinophilia, enhanced IL-5, IL-13, MUC5AC, and eosinophils Major Basic Protein (MBP) production in lung tissue compared to offspring lacking matAbs. Importantly, these unexpected outcomes were not attributed to antibody-dependent enhancement (ADE) resulting from declining matAb levels over time. Notably, our findings showed a decline in secretory IgA (sIgA), mucosal IgA, and mucosal IgG levels in offspring with high matAb levels post-primary RSV challenge. We propose that this decline may be a critical factor contributing to the ineffective protection observed during secondary RSV exposure. Overall, these findings offer valuable insights into maternal vaccination against RSV, contributing to a comprehensive understanding and mitigation of potential risks associated with maternal RSV vaccination.